Examination of the interval between litters (IBL) of different genotype HLW sows using survival analysis - Baginé Hunyadi, Ágnes; Kusza, Szilvia; Balogh, Péter (Acta Agraria Debreceniensis, 2016)
In this study our aim was to find out if there is a difference between the genotypes determined for the previously identified mutations of seven genes of the Hungarian Large White in terms of the time spent in production. We identified the previously determined alleles of the seven genes (BF, EGF, ESR, FSHβ, H2AFZ, LEP, PRLR) related to proliferation that were and performed the survival analysis between breeds indicating the risk of culling and the time spent in production on the given farm. Based on the results of survival analysis by Log-rank test, Breslow (Generalized Wilcoxon) and Tarone-Ware test we concluded that they indicated a significant difference in case of the genes BF (Breslow and Tarone-Ware tests) the EGF (Log-rank and Tarone-Ware tests) and ESR (Log rank test) based on which the curves of the survival of the certain genes varied form one another significantly.